A brief review on the status of machining technology of fir-tree slots on aero-engine turbine disk. (July 2022) - Jianhua, Yu; Xun, Li; Wenshuo, Zhao; Bin, Qin; Yu, Zhang
The machining precision and its consistency of turbine disk fir-tree slots have a direct influence on the performance of aero-engine rotor components. However, the structural dimensions of fir-tree slot are small, and the cutting performance of materials is extremely poor, which lead to great difficulty in machining and very few available machining methods. With the application of new materials in the aero-engines, the machining precision and quality requirements of fir-tree slots are further improved. Therefore, many research achievements on the high-efficiency, high-quality and low-cost machining technology of turbine disk fir-tree slots have been obtained. By summarizing and classifying the machining methods of aero-engine turbine disk fir-tree slots, a brief review on the characteristics of different methods are presented in detail, which provide a reference for selecting the appropriate machining method of turbine disk fir-tree slots in the field of aviation manufacturing. Meanwhile, combined with the research and application status of machining technology of turbine disk fir-tree slots, it is presented that multi-process compound machining is an effective method to realize high-efficiency, high-quality and low-cost precision machining of turbine disk fir-tree slots, such as wire electro discharge machining (wire-EDM) and profiled grinding, wire electrochemical machining (wire-ECM) and profiled grinding, wire-EDM and broaching, milling and broaching.